Barthes - Culler, Jonathan D. (Modern masters., 1983)
This work elucidates the varied theoretical contributions of Barthes. It describes the many projects which he explored, and his contribution to changing the way the public think about a range of cultural phenomena, from literature and fashion, to the notions of the self, of history and of nature.